SEED DEPTH TEST AND APPLICATION OF ECO ENZYME TO THE VEGETATIVE GROWTH OF ARABICA COFFEE PLANTS (Coffea arabica) - Yudi Siswanto; Isnar Sumartono; Muhammad Wasito; Nurloza Khatimah (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Yudi Siswanto, Isnar Sumartono, Nurliza Khatimah. Seed Depth Test and Eco Enzyme Application to the Vegetative Growth of Arabica Coffee Plants (Coffea arabika). The purpose of this study is to determine the depth of seeds and the application of eco enzymes and their interaction with the vegetative growth of Arabica coffee plants (Coffea arabika). This research was carried out in Medan Krio Village, Sunggal District. Deli Serdang Regency. North Sumatra Province with an altitude of ± 30 meters above sea level. This research was carried out from August to November 2025. This study uses a Factorial Group Axak Design (RAK). The first factor is that the depth of the seed is given the symbol "K" which consists of K0 = 0 cm, K1 = 0.5 cm, K2 = 1.0 cm, and K3 = 1.5 cm. The second factor is the application of eco enzymes with the symbol "E" which consists of E0 = 0 ml/liter of water, E1 = 100 ml/liter of water, E2 = 200 ml/liter of water, and E3 = 300 ml/liter of water. The observed parameters are; growth percentage (%), germination time (days), plant height (cm), number of leaves (strands), and stem diameter (mm). The results of the study showed that the seed depth test and the application of eco enzymes had an influence on the parameters, namely: growth percentage (%), germination time (days), plant height (cm), number of leaves (strands), and stem diameter (mm). The interaction of seed depth test and eco enzyme application did not affect the parameters: growth percentage (%), germination time (days), plant height (cm), number of leaves (leaves), and stem diameter (mm).